The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ppa.13462
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, phylogeny, and pathogenicity of Trichothecium, Alternaria, and Fusarium species associated with panicle rot on Chenopodium quinoa in Shanxi Province, China

Abstract: Quinoa panicle rot (QPR) is a novel disease that poses a significant threat to quinoa production in China. Typical symptoms on panicles include a film of pale pink, grey‐white, or dark brown mould on the grains during the grain‐filling stage. Furthermore, QPR causes quinoa grain discolouration, unfilling, and malformation. In total, 37 isolates were identified as belonging to three species: Trichothecium roseum (nine isolates), Alternaria alternata (12), and Fusarium citri (16) based on morphology, and phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The effect of water activity (a w ) on fungal mycelium was examined using the method described by Yin et al (2022) with slight modifications. The a w of the PDA medium was maintained at 0.99, 0.98, 0.97, 0.96, 0.95, 0.94, 0.92, and 0.91 by adding different amounts (v/v) of glycerol (HOCH 2 CHOHCH 2 OH) (Xilong Scientific Co., Ltd. Guangdong, China), and a w was checked three times at 6-h intervals by a Water Activity Meter (AQUA-LAB Dew point a w meter 4TE, PYNN160703) before inoculation.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of water activity (a w ) on fungal mycelium was examined using the method described by Yin et al (2022) with slight modifications. The a w of the PDA medium was maintained at 0.99, 0.98, 0.97, 0.96, 0.95, 0.94, 0.92, and 0.91 by adding different amounts (v/v) of glycerol (HOCH 2 CHOHCH 2 OH) (Xilong Scientific Co., Ltd. Guangdong, China), and a w was checked three times at 6-h intervals by a Water Activity Meter (AQUA-LAB Dew point a w meter 4TE, PYNN160703) before inoculation.…”
Section: Methodsmentioning
confidence: 99%
“…and BenA and CaM ( Aspergillus spp.). For each genus, the sequences of the isolates obtained in the present investigation, as well as those of representative isolates obtained from Genbank, including those of the main Alternaria ( Table S3 ), Penicillium ( Table S4 ), Aspergillus ( Table S5 ), Cladosporium ( Table S6 ) and Fusarium ( Table S7 ) species reported in the literature on C. quinoa ( Table S8 ) [ 18 , 19 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], were used. Moreover, Stemphylium herbarum CBS 191.86 [ 31 ], Talaromyces flavus CBS 310.38 [ 30 ], Cercospora beticola CBS 116,456 [ 56 ] and Neurospora crassa OR74A [ 57 ] were included as outgroups for phylogenetic analysis of Alternaria , Aspergillus and Penicillium , Cladosporium and Fusarium , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, new and emerging quinoa diseases were discovered in new cultivation environments (Colque‐Little et al, 2021). In the last 5 years, seven new quinoa diseases caused by viruses (Sun et al, 2021), oomycetes (Yin et al, 2018) and fungi (Brahmanage et al, 2020; Sun et al, 2018; Yin et al, 2019, 2020, 2022) have been reported in different provinces of China.…”
Section: Introductionmentioning
confidence: 99%
“…incarnatum‐equiseti species complex) in Italy (Beccari et al, 2021), and quinoa panicle rot (caused by F . citri ) in China (Yin et al, 2022). Notably, there has been no detailed research on the species of pathogens associated with Fusarium wilt (Danielsen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation